STUDY ON THE IMPLEMENTATION OF THE CURRICULAR REFORM IN THE FIELD OF INDUSTRIAL CHEMISTRY IN HIGH SCHOOL EDUCATION - Graţian-Daniel GOLOŞIE (Revista de Pedagogie)
Globalization and technological progress require the adaptation of education to the needs of society and the economy. This paper examines the need for a curricular reform in the field of industrial chemistry at high school level. Its main goal is to modernize and streamline the educational process. The study identifies gaps in the current curriculum through document analysis, questionnaires and interviews with teachers, as well as consultations with specialists in the industry. The results emphasize the need to update the school subject content and teaching methods to include scientific discoveries and new technologies. The paper highlights the importance of developing critical skills such as analytical thinking and problem solving. Also, collaboration between education and industry is essential for the practical relevance of the competences to be acquired by the students. The proposed reform integrates application modules, digital technologies and project-based learning. This has the potential to improve student performance, to stimulate interest in chemistry and prepare graduates for industry and research-oriented careers. The conclusions provide recommendations for a holistic and sustained implementation of such curricular reform.